PELATIHAN ASESMEN KOMPETENSI MINIMUM TINGKAT SMP - Risnamirabella Saragih; Khoiruddin Matondang; Yumira Simamora; Jihan Hidayah Putri; Kamal Arief (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2022)
Minimum Competency Assessment (AKM) part of the ANBK examination which is held every year in junior high schools. The purpose of this service is to improve students' skills in solving AKM questions through tryouts. Community service activities were held on June 23 2022 at Bina Satria Mulia Middle School. The target of this activity is class VIII B students with a total of 25 students. The questions given are HOTS questions for junior high school students. This service target has been achieved. Students know the forms of AKM questions, 100% of students take part in the tryout and discussion of AKM questions.